Decomposition of the product of a monomial and a Demazure atom - Ying Pun, Anna (Discrete mathematics and theoretical computer science, 2020)
We prove that the product of a monomial and a Demazure atom is a positive sum of Demazure atoms combinatorially. This result proves one particular case in a conjecture which provides an approach to a combinatorial proof of Schubert positivity property.